Influence of Substituents in the Benzene Ring on the Halogen Bond of Iodobenzene with Ammonia. Issue 6 (11th February 2022) - Scheiner, Steve; Hunter, Sarah
Abstract: The effects on the C−I⋅⋅N halogen bond between iodobenzene and NH3 of placing various substituents on the phenyl ring are monitored by quantum calculations. Substituents R=N(CH3 )2, NH2, CH3, OCH3, COCH3, Cl, F, COH, CN, and NO2 were each placed ortho, meta, and para to the I. The depth of the σ‐hole on I is deepened as R becomes more electron‐withdrawing which is reflected in a strengthening of the halogen bond, which varied between 3.3 and 5.5 kcal mol −1 . In most cases, the ortho placement yields the largest perturbation, followed by meta and then para, but this trend is not universal. Parallel to these substituent effects is a progressive lengthening of the covalent C−I bond. Formation of the halogen bond reduces the NMR chemical shielding of all three nuclei directly involved in the C−I⋅⋅N interaction. The deshielding of the electron donor N is most closely correlated with the strength of the bond, as is the coupling constant between I and N, so both have potential use as spectroscopic measures of halogen bond strength. Abstract : Substituent effects : Substituents ortho, meta, and para to the I atom of iodobenzene affect the I⋅⋅N halogen bond with NH3 . Ortho placement has the largest effect and para the smallest. The halogen bond strength correlates with various structural and electronic properties. Most tightly correlated of the NMR spectral parameters are the chemical shifts of the C and N atoms that bracket the I, and coupling constant between I and N.